2018
DOI: 10.3390/ma12010084
|View full text |Cite
|
Sign up to set email alerts
|

Direct Formation and Structural Characterization of Electride C12A7

Abstract: Ca12Al14O33 (C12A7 or Mayenite) is a material whose caged clathrate structure and occluded anionic species leads to significant functionality. The creation of occluded anionic vacancies leads to the injection of localized electrons at the center of the cage, converting the wide band gap insulator to a semi- or metallic conducting material. The conversion to the electride historically requires the synthesis of oxy-C12A7, consolidation, and then reduction to introduce anionic vacancies. This report develops and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…When Ca 12 Al 13 GaO 33 was subjected to reducing conditions at 1350 °C for 6 h, buried in graphite powder, the compound decomposed to Ca 3 Al 2 O 6 and Ca 12 Al 14−x Ga x O 33 7 . The cause of decomposition is not known, but Ca 12 Al 14 O 33 structure in general demonstrates complicated thermodynamic instability/stability trends under dry reducing conditions above 1100 °C 8 , 9 . The influence of Ga on the cage structure and localized electron behavior could alter the physical properties including the mobility of occluded species, either atomic, molecular, or electrons, and the electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…When Ca 12 Al 13 GaO 33 was subjected to reducing conditions at 1350 °C for 6 h, buried in graphite powder, the compound decomposed to Ca 3 Al 2 O 6 and Ca 12 Al 14−x Ga x O 33 7 . The cause of decomposition is not known, but Ca 12 Al 14 O 33 structure in general demonstrates complicated thermodynamic instability/stability trends under dry reducing conditions above 1100 °C 8 , 9 . The influence of Ga on the cage structure and localized electron behavior could alter the physical properties including the mobility of occluded species, either atomic, molecular, or electrons, and the electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Though this process leads to dense ceramics well suited for electrical applications, the scale-up potential to obtain large amounts of powder material necessary for an application as a catalyst support seems challenging. Similar to studies by Khan et al, Salasin et al and Li et al showed the possibility to obtain electrides by synthesis from different Ca and Al precursor compounds and not the preformation of C12A7 [33][34][35][36][37][38] . A big step towards the batch synthesis of larger amounts of C12A7e -, in respect of an application as a catalyst support, was accomplished by Jiang et al by aluminothermic synthesis using a mixture of CaO, Al 2 O 3 and Al and heating under Ar at 1373 K for 8 h 39 .…”
Section: Introductionmentioning
confidence: 57%
“…N e reached the maximum value when addition amount was 1.58% and then decreased as the increase of addition amount. Previous reports demonstrated that the relation between N e within the as‐sintered C12A7:e − and the peak position can be described by the following equation:Nnormale=][-)(Esp-Esp0false/0.1190.782where E sp 0 = 2.83 eV corresponds to the peak position of absorption peak at N e = 1×10 18 cm −3 . The highest electron concentration estimated from the above formula was 2.13 × 10 21 cm −3 , which had a little error to the theory value (2.33 × 10 21 cm −3 ).…”
Section: Resultsmentioning
confidence: 90%
“…where E sp 0 = 2.83 eV corresponds to the peak position of absorption peak at N e = 1×10 18 cm −3 . 25 The highest electron concentration estimated from the above formula was 2.13 × 10 21 cm −3 , which had a little error to the theory value (2.33 × 10 21 cm −3 ). Notably, the spins concentration estimated from EPR is merely a fraction of the N e .…”
Section: Characterization Techniquesmentioning
confidence: 77%